A cinemática e distribuição do gás molecular e ionizado na região central da galáxia Seyfert NGC1125 - Marques, Johan Matheus (2021)
We use the J and K spectroscopic observations of the inner 350 pc of the Seyfert 2 galaxy NGC1125 to investigate the kinematic structure of the hot molecular ( 2000 K) and ionized gas, as well as of the stars. The spectroscopic data have been obtained from the Gemini North telescope, using the NIFS instrument, and have a spatial resolution of approximately 80 pc and a spectral resolution of 50 km s1. The stellar kinematics was obtained from the fitting of CO absorption bands at 2.3 m and the stellar velocity field shows a rotation pattern well reproduced by a disk model. The gas excitation and kinematics were studied from the fitting of the [Fe II], [P II], H2 and H recombination emission lines, by a Gauss-Hermite series and by Gaussian functions. The excitation of the H2 and [Fe II] emission lines is possibly due to shocks and due the radiation field from the the active nucleus. The velocity field of the molecular gas is dominated by a rotation component in the galaxy’s plane, similar to that of the stars, while the ionized gas also shows a bipolar outflow, with velocities of 150 kms1. This outflow interacts with the gas in the disk, producing a hot molecular gas outflow, seen only in the galaxy’s nucleus. The masses of the hot molecular and ionized gases in the outflow are 45 M and 4.3 104 M , respectively. These values correspond to about 32% of all the ionized gas and 15% of the hot molecular gas present in the central region of the galaxy. Assuming a biconical geometry, we estimate an outflow rate in ionized gas of _Mout 6.0 103 M /yr1 and a kinectic power of _Ekin 4.5 1038 erg s1, indicating that the observed outflows of NGC1125 are not powerful enough to impact the star formation in the host galaxy, but can be efficient to redistribute the gas in its central region.